A further note on the unsteady mixed convection boundary layer in a porous medium with temperature slip: An exact solution - Merkin, John H.; Pop, Ioan; Mohd Rohni, Azizah; Ahmad, Syakila (Springer Netherlands, 2012)
The aim of this Letter is to show that a further exact solution of the problem on unsteady mixed convection boundary layer in a porous medium with temperature slip can be obtained in addition of that reported very recently by Fang et al. (2012).